Information Seeking Behavior of Users on Electronic Resourcesduring the Period of Pandemic (COVID-19) in the University Libraries of Pakistan - Zafar, Irfan; Ahmedani, Aijaz Akhtar; Shahzeb; Abro, Irfan Ali; Shaikh, Muhammad Naeem (The journal of contemporary issues in business and government, 2021)
The purpose of this study is to examine the user behavior to use electronic resources during period of pandemic: A case study of Public sector University libraries in Sindh Province. It also examines the available collection of electronic resources and facilities provided by the library to access those electronic resources during the period of Pandemic (COVID-19). Methods: - The study was based on descriptive design. The population of the study was Public sector University libraries users.Sample random sampling technique was used to collect data from the respondents of different degree programs. This five-point scale questionnaire was used as instrument of data collection. SPSS-21 was used for statistical analysis.Findings:- The users were interested in accepting the technology as well as gaining knowledge by accessing e-resources. The study found that users were generally satisfied with their library digital collections like e-books, e- journals, institutional repositories, e-magazines and e-dailies. At the same the study observed that the respondents are satisfied with library.